Maintaining higher leaf photosynthesis after heading stage could promote biomass accumulation in rice - Honda, Sotaro; Ohkubo, Satoshi; San, Nan Su; Nakkasame, Anothai; Tomisawa, Kazuki; Katsura, Keisuke; Ookawa, Taiichiro; Nagano, Atsushi J.; Adachi, Shunsuke (Scientific reports, 2021)
Leaf photosynthetic rate changes across the growing season as crop plants age. Most studies of leaf photosynthesis focus on a specific growth stage, leaving the question of which pattern of photosynthetic dynamics maximizes crop productivity unanswered. Here we obtained high-frequency data of canopy leaf CO 2 assimilation rate ( A ) of two elite rice ( Oryza sativa ) cultivars and 76 inbred lines across the whole growing season. The integrated A value after heading was positively associated with crop growth rate (CGR) from heading to harvest, but that before heading was not. A curve-smoothing analysis of A after heading showed that accumulated A at > 80% of its maximum ( A 80 ) was positively correlated with CGR in analyses of all lines mixed and of lines grouped by genetic background, while the maximum A and accumulated A at ≤ 80% were less strongly correlated with CGR. We also found a genomic region (~ 12.2 Mb) that may enhance both A 80 and aboveground biomass at harvest. We propose that maintaining a high A after heading, rather than having high maximum A , is a potential target for enhancing rice biomass accumulation.